Design Modification and Strength Analysis of a Bearing Housing Using Finite Element Method - Mulyadi Mulyadi; Bobby Umroh; Hendery Dahlan (Rekayasa Material, Manufaktur dan Energi, 2026)
Bearing housings are critical mechanical components in small-scale manufacturing machinery. In field operations, standard pillow block designs frequently experience premature structural failures such as material cracking and high deformation under dynamic loads. This study aims to determine the exact structural causes of failure in standard bearing housings used within chain transmission systems and to develop an optimized, structurally superior modified design. The investigation was conducted numerically using open-source tools: FreeCAD for three-dimensional parametric modeling and PrePoMax (CalculiX solver) for Finite Element Analysis (FEA). The component was modeled using ASTM Class 35 Cast Iron with a yield strength of 170 MPa. The loading condition simulated a 1 HP motor running at 1500 rpm with a generated torque of 1.59 kg·m, where the chain tensile force was applied directly to the housing bore. The initial simulation revealed that the baseline design suffered from high stress concentrations around the bolt hole and fillet regions due to insufficient material thickness. The maximum principal stress reached 107.4 MPa, yielding an inadequate safety factor of 1.6 and a displacement of 0.002 mm. To resolve this, structural modifications were implemented by adding reinforcing ribs and thickening the housing profile. The FEA results of the modified design showed a significant stress reduction to 55 MPa (a decrease of approximately 49%). Furthermore, the maximum displacement at the top section dropped to 0.0009 mm, demonstrating a 45% reduction in displacement and higher structural stiffness. Consequently, the safety factor increased substantially from 1.6 to 3.6 (simulated at 3.09 in direct stress ratio). The incorporation of strengthening ribs and wall thickening successfully redistributes operational loads and minimizes material distortion. The modified design satisfies industrial safety regulations and is highly feasible for implementation in small-scale industrial chain drive applications.Keywords: Bearing Housing, Finite Element Method, Stress Concentration, Reinforcing Ribs, Safety Factor.